A comparative longitudinal study between bilateral and unilateral totally extraperitoneal repair among patients with unilateral inguinal hernia at a tertiary care hospital in eastern Nepal - Bikash Kumar Sah; Jatin Goel; Vijay Pratap Sah; Bhawani Khanal; Abhijeet Kumar; Rakesh Kumar Gupta (International Journal of Abdominal Wall and Hernia Surgery)
INTRODUCTION: It has been reported that there is a significantly high chance of contralateral concurrent occult or subsequent inguinal hernia in patients with unilateral inguinal hernia. The objective of this study is to investigate the feasibility of bilateral laparoscopic exploration for all unilateral cases followed by laparoscopic bilateral total extraperitoneal repair and to compare complications, recurrence rates, postoperative pain, and operative duration with prospectively performed unilateral repairs. MATERIALS AND METHODS: A total of 60 patients were included in this prospective longitudinal study from March 2018 to March 2019. Patients attending the outpatient department for unilateral inguinal hernia were counseled about the trial. Patients who gave consent for bilateral inguinal exploration and repair were kept in group A, and those who did not consent to bilateral exploration and underwent unilateral repair were kept in group B. The patients were divided into two groups of 30 patients each. RESULTS: The mean age of patients in group A was 36.57 ± 11.80 years and in group B was 43.03 ± 13.106 years (P = 0.049). The incidence of occult contralateral hernia is 26.7%, with the most common on the left side (33.3%). It was found that the duration of surgery for group A (82 ± 4.74 min) was longer than that for group B (66.30 ± 6.27 min) with a P value of 0.001. Intraoperative blood loss in the case of group B was 16.63 ± 2.341 ml, and for group A, it was 20.03 ± 2.671 ml (P < 0.001). No major complications were observed. There was no significant difference in pain upto a 1-month follow-up in both groups. No recurrence or pain was noticed in either group at 3 and 6 months. CONCLUSION: There is no significant difference in pain, complications, and recurrence between both groups, with one-fourth of patients having OCH. Young to middle-aged patients can easily tolerate the longer operative time at the cost of slightly more blood loss. Thus, selected patients with unilateral hernias can be given the option of bilateral repair with no added risk associated with surgery. Trial registration: ClinicalTrials.gov, identifier NCT06380621.